Neonatal head injuries. Issue 5 (1st September 2000) - Graham, Colin A; O'Toole, Stuart J; Haddock, Graham
Abstract : A retrospective case note review of head injuries in neonates admitted to the Neonatal Surgical Unit in Glasgow between 1990 and 1996 (n=25) was carried out. Most injuries were caused by a fall (68%) and resulted in scalp haematomata and associated skull fractures in the majority of patients. Three neonates were involved in high speed road traffic accidents, and these infants all had intracranial pathology identified by computed tomography. Isolated skull fractures were common and did not appear to be associated with any neurological deficit. Non-accidental injury was uncommon in this age group. Outcome was excellent in the majority of patients (92%).